Peran Perusahaan dalam Penguatan UMKM dan Implikasinya terhadap Manajemen Pendidikan Berbasis Masyarakat di Bontang - Irianto (Manajemen Pendidikan Program Doktor, 2025)
This study examines the role of large companies in empowering micro, small, and medium enterprises (MSMEs) in Bontang City and analyzes its broader implications for educational management, particularly within community-based learning frameworks. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis involving company representatives, MSME actors, government agencies, and educational practitioners. The findings indicate that corporate empowerment programs—including training, mentoring, market facilitation, and financial assistance—significantly improve MSME managerial skills, digital literacy, product quality, and business networks. Beyond economic impacts, these empowerment activities function as community-based nonformal education that supports lifelong learning and strengthens local human resource development. The collaboration among companies, local government, digital communities, and educational institutions forms a sustainable learning ecosystem that integrates industrial experience into vocational education, entrepreneurship programs, and community learning centers. This synergy demonstrates that corporate involvement plays a strategic role not only in regional economic development but also in enhancing educational capacity, literacy, and community empowerment. The study concludes that MSME empowerment initiatives contribute meaningfully to educational management by promoting experiential learning, strengthening community competencies, and supporting inclusive development aligned with digital-era demands.